Structure and electronic properties of (+)-catechin : aqueous solvent effects - Bentz, Erika Natalia (2014)
Fil: Bentz, Erika Natalia. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.